Preparation method for synthesizing copper-zinc-based catalyst by ammonia circulation method

The preparation method of synthesis of copper-zinc-based catalysts by ammonia cycle method has solved the problems of more wastewater, high energy consumption and difficult impurities treatment in the prior art, achieved efficient raw material utilization and low-cost production, and improved the purity and performance of the catalyst.

CN119746868APending Publication Date: 2025-04-04ANHUI CONCH IND TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411934118.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, there are more wastewater and waste gases in the preparation process of copper-zinc catalysts, which consume more energy and cost, and impurities in the raw materials are difficult to be treated, which affects the purity of the catalyst and the utilization rate of the raw materials.

Method used

The preparation method of synthesis of copper-zinc-based catalysts by ammonia cycle method is used to dissolve copper-containing solids, zinc-containing solids and ammonia-containing substances in the solvent, and the cupric-zinc-ammonia solution is obtained after filtration, additives are added and heated, water vapor or carbon dioxide is introduced, ammonia is vaporized and degassed, and the catalyst is obtained after precipitation filtering, washing, drying and calcining.

Benefits of technology

It improves the utilization rate of raw materials, reduces the consumption of acids and alkalis, does not produce pollutants such as nitrogen oxides and sodium nitrate, reduces production costs, and effectively prevents harmful impurities in the raw materials from entering the catalyst, and uses a wider range of raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211076430000081
    Figure BDA0005211076430000081
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst preparation, and particularly relates to a preparation method for synthesizing a copper-zinc-based catalyst by an ammonia circulation method, which comprises the following steps: dissolving a copper-containing solid, a zinc-containing solid and an ammonia-containing substance in a solvent, and filtering to obtain a copper ammonia-zinc ammonia solution; adding an auxiliary agent into the copper ammonia-zinc ammonia solution; heating the copper ammonia-zinc ammonia solution, simultaneously introducing water vapor or carbon dioxide or mixed gas of the water vapor and the carbon dioxide, vacuumizing to maintain negative pressure, gasifying ammonia to be separated from a solution system, generating precipitates in the solution, condensing or washing gasified ammonia obtained by vacuumizing to generate ammonia water, and recycling the ammonia water; and filtering out the precipitate, washing a filter cake with deionized water, and drying, roasting and carrying out compression molding on the filter cake to obtain the catalyst. Pollutants and byproducts such as nitric oxide and sodium nitrate are not generated, and the production cost is reduced. Meanwhile, the method has the effect similar to recrystallization, harmful impurities in the raw materials can be prevented from entering the final catalyst, and the raw materials with low purity can be directly utilized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a method for preparing a copper-zinc-based catalyst synthesized by an ammonia circulation method. Background Art

[0002] Copper-zinc catalysts have a wide range of applications, including but not limited to industrial methanol synthesis, low-temperature water-gas shift reaction, steam reforming hydrogen production reaction, biomass conversion reaction, carbon dioxide hydrogenation to methanol, etc. There is a synergistic effect between copper and zinc. The larger the copper-zinc interface, the better the catalytic performance. In order to make copper and zinc mix evenly at the atomic scale, the prior art usually adopts a coprecipitation method to prepare copper-zinc-based catalysts to generate zinc malachite structure or green covellite structure. For example, the catalyst for industrial methanol synthesis is a solution of copper nitrate, zinc nitrate, and aluminum nitrate prepared by dissolving metallic copper, metallic zinc, and metallic aluminum in nitric acid, and then reacting with a sodium carbonate solution to produce a precipitate, which is then obtained by aging, filtering, washing, drying, roasting, and molding. The reaction process consumes nitric acid and sodium carbonate, and produces nitrogen oxides, carbon dioxide and wastewater containing sodium nitrate. Environmental protection equipment for nitrogen oxide absorption and sodium nitrate wastewater treatment is required, which greatly increases the energy consumption and cost of production. At the same time, the existing technology is less effective in treating impurities in raw materials, and it is difficult to prevent some harmful impurities in the raw materials from entering the catalyst. Therefore, the purity of the catalyst is greatly affected by the raw materials, which reduces the purity of the catalyst product, reduces the utilization rate of the raw materials, and also limits the types and sources of raw materials. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a copper-zinc-based catalyst synthesized by an ammonia circulation method, so as to solve the technical problems in the prior art of generating a large amount of waste water and waste gas, high energy consumption and cost, and difficulty in treating impurities in raw materials.

[0004] The method for preparing a copper-zinc-based catalyst synthesized by an ammonia circulation method comprises:

[0005] The copper-containing solid, the zinc-containing solid and the ammonia-containing substance are dissolved in a solvent, and a copper-ammonia-zinc-ammonia solution is obtained after filtering.

[0006] Add additives to the copper ammonia-zinc ammonia solution.

[0007] The copper ammonia-zinc ammonia solution is heated, and water vapor or carbon dioxide or a mixture of the two is introduced at the same time, and vacuum is drawn to maintain negative pressure, so that the ammonia is gasified and separated from the solution system, and precipitation is generated in the solution. The gasified ammonia obtained by vacuum drawing is condensed or washed with water to generate ammonia water and recycled.

[0008] The precipitate is filtered out and the filter cake is washed with deionized water. The filter cake is dried, calcined and pressed into a shape to obtain a catalyst.

[0009] Preferably, the auxiliary agent includes any one of aluminum oxide, aluminum hydroxide, aluminum nitrate, zirconium oxide, zirconium hydroxide, zirconium nitrate, magnesium oxide, magnesium hydroxide, and magnesium nitrate, or a mixture of several of them.

[0010] Preferably, the solvent is any one of water, methanol and ethanol or a mixture of several of them.

[0011] Preferably, the ammonia-containing substance is any one of ammonia, ammonium carbonate, ammonium bicarbonate, and urea, or a mixture of several of them.

[0012] Preferably, the copper-containing solid is any one of metallic copper, copper oxide, cuprous oxide, cupric hydroxide, cuprous hydroxide, basic copper carbonate, copper nitrate, and copper ore, or a mixture of several of them.

[0013] Preferably, the zinc-containing solid is any one of metallic zinc, zinc oxide, zinc hydroxide, zinc carbonate, basic zinc carbonate, zinc nitrate, and zinc ore, or a mixture of several of them.

[0014] Preferably, the temperature of heating the copper ammonia-zinc ammonia solution is controlled between 45-90° C., and the vacuum degree is controlled between 0.01-0.1 MPa during vacuuming.

[0015] Preferably, the drying temperature of the filter cake is 60-150°C, and the calcination temperature is 280-350°C.

[0016] The present invention has the following advantages: compared with the traditional coprecipitation method, the raw material utilization rate of the present method is higher, no acid and alkali are consumed in the process, no pollutants and by-products such as nitrogen oxides and sodium nitrate are generated, and the precipitate does not need to be repeatedly washed and impurity-removed, which saves the investment in environmental protection equipment and reduces production costs. At the same time, the present method has similar effects to recrystallization, and can prevent harmful impurities in the raw materials from entering the final catalyst. Therefore, the present method can utilize a wider range of raw materials, and can directly utilize raw materials with lower purity such as ores and waste catalysts.

[0017] This method innovatively uses a mixed solution of methanol, ethanol and water when preparing a copper ammonia-zinc ammonia solution, which can reduce the time and temperature for removing ammonia, and the obtained catalyst also has a larger specific surface area and catalytic activity. It also innovatively introduces a small amount of carbon dioxide during the ammonia evaporation process to supplement carbonate ions, thereby stabilizing highly active intermediates such as zinc malachite, thereby improving catalytic performance in various aspects. As for the auxiliary agents of the reaction, several embodiments of this scheme respectively use structural auxiliary agents represented by aluminum oxide to disperse copper and zinc; use auxiliary agents such as zirconium oxide and zirconium hydroxide to activate carbon dioxide, so that the conversion rate of the catalyst and the methanol space-time yield are both high; and use strong alkaline auxiliary agents such as magnesium oxide to improve the methanol selectivity of the catalyst. DETAILED DESCRIPTION

[0018] The specific implementation modes of the present invention are further explained in detail below through the description of embodiments, so as to help those skilled in the art to have a more complete, accurate and in-depth understanding of the inventive concept and technical solution of the present invention.

[0019] The invention provides a method for preparing a copper-zinc-based catalyst synthesized by an ammonia circulation method, comprising the following steps.

[0020] Dissolve copper-containing solids, zinc-containing solids and ammonia-containing substances in a solvent, and obtain a copper-ammonia-zinc-ammonia solution after filtering. The copper-containing solid is any one or a mixture of metallic copper, copper oxide, cuprous oxide, copper hydroxide, cuprous hydroxide, basic copper carbonate, copper nitrate, and copper ore. The zinc-containing solid is any one or a mixture of metallic zinc, zinc oxide, zinc hydroxide, zinc carbonate, basic zinc carbonate, zinc nitrate, and zinc ore. The solvent is any one or a mixture of water, methanol, and ethanol. The ammonia-containing substance is any one or a mixture of ammonia, ammonium carbonate, ammonium bicarbonate, and urea.

[0021] Add an auxiliary agent to the copper ammonia-zinc ammonia solution. The auxiliary agent is any one or a mixture of aluminum oxide, aluminum hydroxide, aluminum nitrate, zirconium oxide, zirconium hydroxide, zirconium nitrate, magnesium oxide, magnesium hydroxide, and magnesium nitrate.

[0022] The copper ammonia-zinc ammonia solution is heated, and water vapor or carbon dioxide or a mixture of the two is introduced at the same time, and vacuum is drawn to maintain negative pressure, so that ammonia is gasified and separated from the solution system, and precipitation is generated in the solution. The gasified ammonia obtained by vacuuming is condensed or washed to generate ammonia water and recycled. The temperature of heating the copper ammonia-zinc ammonia solution is controlled between 45-90°C, and the vacuum degree is controlled between 0.01-0.1MPa during vacuuming. The process of extracting ammonia will take away water vapor at the same time, so adding water vapor to the space can reduce the water loss of the solution. By regulating the temperature of the water vapor, it can provide heat while replenishing water, so that the temperature in the evaporation system is relatively stable. The gas introduced can also be air, or a mixture of any one or more of air, water vapor, and carbon dioxide.

[0023] The precipitate is filtered out and the filter cake is washed with deionized water, and the filter cake is dried, calcined, and pressed to obtain a catalyst. The drying temperature is 60-150°C, and the calcination temperature is 280-350°C.

[0024] After adopting the above-mentioned preparation method based on the ammonia circulation method, compared with the traditional coprecipitation method, the raw material utilization rate of this method is higher, no acid and alkali are consumed in the process, no pollutants and by-products such as nitrogen oxides and sodium nitrate are generated, and the precipitate does not need to be repeatedly washed and impurity-removed, which saves the investment in environmental protection equipment and reduces production costs. At the same time, this method has similar effects to recrystallization, which can prevent harmful impurities in the raw materials from entering the final catalyst. Therefore, this method can use a wider range of raw materials and can directly use raw materials with lower purity such as ores and waste catalysts. The specific embodiments of this scheme are as follows.

[0025] Example 1.

[0026] Weigh 11.055 g of basic copper carbonate (containing copper solid), 5.99 g of basic zinc carbonate (containing zinc solid), and 48 g of ammonium carbonate (containing ammonia substance), add 150 g of deionized water (solvent), stir and dissolve, and filter to obtain solution A (copper ammonia-zinc ammonia solution).

[0027] After adding 7.155 g of zirconium nitrate pentahydrate (auxiliary agent) to solution A, stir and heat to 80°C, pass a small amount of water vapor and connect a vacuum pump, control the vacuum degree in the container of solution A between 0.01-0.1 MPa, boil the solution for 5 hours, and obtain a precipitate.

[0028] The precipitate was filtered out, washed with 500 mL of deionized water, dried at 110° C. for 12 hours, calcined at 300° C. for 3 hours, and pressed into tablets to obtain catalyst sample 1.

[0029] Example 2.

[0030] Weigh 6.35 g of metallic copper (containing copper solid), 4.05 g of zinc oxide (containing zinc solid), 24 g of ammonium carbonate, 15.2 g of ammonium bicarbonate and 10 mL of ammonia water (containing ammonia substance), add 150 g of deionized water (solvent) and stir to dissolve, and filter to obtain solution A (copper ammonia-zinc ammonia solution).

[0031] After adding 2.64 g of zirconium hydroxide (auxiliary agent) to solution A, stir and heat to 75°C, pass a small amount of water vapor and connect a vacuum pump, control the vacuum degree in the container of solution A between 0.01-0.1 MPa, boil the solution for 5 hours, and obtain a precipitate.

[0032] The precipitate was filtered out, washed with 500 mL of deionized water, dried at 110° C. for 12 hours, calcined at 300° C. for 3 hours, and pressed into tablets to obtain catalyst sample 2.

[0033] Example 3.

[0034] Weigh 24.16 g of copper nitrate (containing copper solid), 14.85 g of zinc nitrate (containing zinc solid), and 76.8 mL of ammonia water (containing ammonia substance), add 150 g of deionized water (solvent) and stir to dissolve, and filter to obtain solution A (copper ammonia-zinc ammonia solution).

[0035] After adding 4.8 g of zirconium oxide (auxiliary agent) to solution A, stir and heat to 90°C, introduce a small amount of water vapor and connect a vacuum pump, control the vacuum degree in the container of solution A between 0.01-0.1 MPa, boil the solution for 5 hours, and obtain a precipitate.

[0036] The precipitate was filtered out, washed with 3000 mL of deionized water, dried at 110° C. for 12 hours, calcined at 300° C. for 3 hours, and pressed into tablets to obtain catalyst sample 3.

[0037] Example 4.

[0038] Weigh 7.9 g of copper oxide (containing copper solid), 5.1 g of zinc hydroxide (containing zinc solid), 45.6 g of ammonium bicarbonate and 20 mL of ammonia water (containing ammonia substance), add 150 g of deionized water (solvent) and stir to dissolve, and filter to obtain solution A (copper ammonia-zinc ammonia solution).

[0039] After adding 2.64 g of zirconium hydroxide (auxiliary agent) to solution A, stir and heat to 60°C, pass a small amount of water vapor and connect a vacuum pump, control the vacuum degree in the container of solution A between 0.01-0.1 MPa, boil the solution for 12 hours to obtain a precipitate.

[0040] The precipitate was filtered out, washed with 3000 mL of deionized water, dried at 60° C. for 12 hours, calcined at 330° C. for 3 hours, and pressed into tablets to obtain catalyst sample 4.

[0041] Example 5.

[0042] Weigh 31.8 g of copper ore (containing copper solid), 15.1 g of zinc ore (containing zinc solid), and 48 g of ammonium carbonate (containing ammonia substance), add 150 g of deionized water (solvent), stir and dissolve, and filter to obtain solution A (copper ammonia-zinc ammonia solution).

[0043] After adding 2.64 g of zirconium hydroxide (auxiliary agent) to solution A, stir and heat to 75°C, pass a small amount of water vapor and connect a vacuum pump, control the vacuum degree in the container of solution A between 0.01-0.1 MPa, boil the solution for 12 hours to obtain a precipitate.

[0044] The precipitate was filtered out, washed with 500 mL of deionized water, dried at 110° C. for 12 hours, calcined at 280° C. for 3 hours, and pressed into tablets to obtain catalyst sample 5.

[0045] Example 6.

[0046] Weigh 11.055 g of basic copper carbonate (containing copper solid), 5.99 g of basic zinc carbonate (containing zinc solid), and 48 g of ammonium carbonate (containing ammonia substance), add a mixed liquid (solvent) of 150 g of deionized water, 20 mL of methanol, and 30 mL of ethanol, stir and dissolve, and filter to obtain solution A (copper ammonia-zinc ammonia solution).

[0047] After adding 7.155 g of zirconium nitrate pentahydrate (auxiliary agent) to solution A, stir and heat to 70°C, pass a small amount of water vapor and connect a vacuum pump, control the vacuum degree in the container of solution A between 0.01-0.1 MPa, boil the solution for 3 hours, and obtain a precipitate.

[0048] The precipitate was filtered out, washed with 500 mL of deionized water, dried at 110° C. for 12 hours, calcined at 300° C. for 3 hours, and pressed into tablets to obtain catalyst sample 6.

[0049] Example 7.

[0050] Weigh 11.055 g of basic copper carbonate (containing copper solid), 5.99 g of basic zinc carbonate (containing zinc solid), and 48 g of ammonium carbonate (containing ammonia substance), add 150 g of deionized water (solvent), stir and dissolve, and filter to obtain solution A (copper ammonia-zinc ammonia solution).

[0051] After adding 0.85 g of aluminum oxide (auxiliary agent) to solution A, stir and heat to 75°C, pass a small amount of water vapor and connect a vacuum pump, control the vacuum degree in the container of solution A between 0.01-0.1 MPa, boil the solution for 5 hours, and obtain a precipitate.

[0052] The precipitate was filtered out, washed with 500 mL of deionized water, dried at 110° C. for 12 hours, calcined at 300° C. for 3 hours, and pressed into tablets to obtain catalyst sample 7.

[0053] Example 8.

[0054] Weigh 11.055 g of basic copper carbonate (containing copper solid), 5.99 g of basic zinc carbonate (containing zinc solid), and 48 g of ammonium carbonate (containing ammonia substance), add 150 g of deionized water (solvent), stir and dissolve, and filter to obtain solution A (copper ammonia-zinc ammonia solution).

[0055] After adding 0.85 g of magnesium oxide (auxiliary agent) to solution A, stir and heat to 75°C, pass a small amount of water vapor and connect a vacuum pump, control the vacuum degree in the container of solution A between 0.01-0.1 MPa, boil the solution for 5 hours, and obtain a precipitate.

[0056] The precipitate was filtered out, washed with 500 mL of deionized water, dried at 110° C. for 12 hours, calcined at 300° C. for 3 hours, and pressed into tablets to obtain catalyst sample 8.

[0057] Example 9.

[0058] Weigh 11.055 g of basic copper carbonate (containing copper solid), 5.99 g of basic zinc carbonate (containing zinc solid), and 48 g of ammonium carbonate (containing ammonia substance), add 150 g of deionized water (solvent), stir and dissolve, and filter to obtain solution A (copper ammonia-zinc ammonia solution).

[0059] After adding 7.155 g of zirconium nitrate pentahydrate (auxiliary agent) to solution A, stir and heat to 80°C, pass a small amount of mixed gas of water vapor and carbon dioxide and connect a vacuum pump, control the vacuum degree in the container of solution A between 0.01-0.1 MPa, boil the solution for 7 hours, and obtain a precipitate.

[0060] The precipitate was filtered out, washed with 500 mL of deionized water, dried at 110° C. for 12 hours, calcined at 300° C. for 3 hours, and pressed into tablets to obtain catalyst sample 9.

[0061] As a comparative example, the applicant also conducted the following experiments.

[0062] Comparative example 1.

[0063] Weigh 36.25 g of copper nitrate trihydrate (containing copper solid), 16.47 g of zinc acetate dihydrate (containing zinc solid), and 10.59 g of zirconium nitrate pentahydrate, add 150 g of deionized water (solvent), stir and dissolve, and filter to obtain solution A. Weigh 26.50 g of sodium carbonate, add 300 g of deionized water, stir and dissolve, and obtain alkaline solution B.

[0064] Heat the alkaline solution B to 70°C, add solution A to the alkaline solution B while stirring, and maintain the reaction temperature at 70°C. When the pH drops to 6.5, stop adding solution A, and maintain aging at 70°C for 2 hours.

[0065] The aged product was filtered and washed with deionized water until no Na ions were detected. The filter cake was dried at 110° C. for 12 hours, calcined at 300° C. for 3 hours, and pressed into tablets to obtain catalyst sample 10.

[0066] Comparative example 2.

[0067] Weigh 11.055 g of basic copper carbonate (containing copper solid), 5.99 g of basic zinc carbonate (containing zinc solid), and 48 g of ammonium carbonate (containing ammonia substance), add 150 g of deionized water (solvent), stir and dissolve, and obtain solution A (copper ammonia-zinc ammonia solution).

[0068] Solution A was stirred and heated to 80°C, a small amount of mixed gas of water vapor and carbon dioxide was introduced and a vacuum pump was connected, the vacuum degree in the container of solution A was controlled between 0.01-0.1 MPa, the solution was boiled for 5 hours, and a precipitate was obtained.

[0069] The precipitate was filtered out and washed with 500 mL of deionized water. The filter cake was dried at 110° C. for 12 hours, calcined at 300° C. for 3 hours, and pressed into tablets to obtain catalyst sample 11.

[0070] Comparative example 3.

[0071] Weigh 11.055 g of basic copper carbonate (containing copper solid) and 48 g of ammonium carbonate (containing ammonia substance), add 150 g of deionized water (solvent) and stir to dissolve, to obtain solution A.

[0072] After adding 7.155 g of zirconium nitrate pentahydrate to solution A, stir and heat to 80°C, introduce a small amount of water vapor and connect a vacuum pump, control the vacuum degree in the container of solution A between 0.01-0.1 MPa, boil the solution for 5 hours, and obtain a precipitate.

[0073] The precipitate was filtered out and washed with 500 mL of deionized water. The filter cake was dried at 110° C. for 12 hours, calcined at 300° C. for 3 hours, and pressed into tablets to obtain catalyst sample 12.

[0074] The experimental products of the above embodiments are tested for relevant properties, including: catalytic performance test: the catalyst is tested for activity using a fixed bed high pressure micro-reaction device, and the product composition is analyzed by a gas chromatograph to calculate the selectivity of the reaction and the time-space yield of methanol. Specifically, the catalyst samples of each embodiment and comparative example are crushed and passed through a 40-80 mesh sieve, and then 0.1g is weighed and mixed with 0.4g of quartz sand and loaded into a fixed bed reactor. Before the activity test, the catalyst is subjected to in-situ temperature reduction in an atmosphere of 20% H2-80% Ar by volume, and reduced at 250°C for 1 hour. Synthetic methanol reaction conditions: reaction pressure is 2.0MPa, reaction temperature is 220°C, and space velocity is 24000h-1; raw gas volume composition: CO2=24%, Ar=4%, and the rest is H2. The test results are shown in Table 1.

[0075] Table 1: Performance test results of catalyst samples

[0076]

[0077] As can be seen from the above, the catalytic performance and specific surface area of ​​the samples obtained in Examples 1 to 4 are substantially the same, indicating that different raw materials of copper, zinc and ammonia can be used to obtain copper ammonia-zinc ammonia solutions after dissolution, and the solutes are mainly composed of copper ammonia ions, zinc ammonia ions, carbonate ions, hydroxide ions and free ammonia. After that, ammonia is separated from the solution system to obtain a copper-zinc-based catalyst. In order to avoid the introduction of impurity ions in the preparation, simple substances, oxides, hydroxides and carbonates of copper and zinc are preferred.

[0078] In Example 5, copper ore and zinc ore are used as raw materials, wherein the main impurities are silicon oxide, aluminum oxide, iron oxide, calcium carbonate, etc. These impurities are insoluble in ammonia solution and can be separated by filtration to obtain a high-purity copper-ammonia-zinc-ammonia solution. Therefore, in Example 5, not only can a catalyst structure with copper and zinc tightly combined be obtained during the ammonia circulation process, but also the raw material purification function can be achieved.

[0079] In Example 6, a mixed solution of methanol, ethanol and water is used. Compared with pure water, the mixed solution has a lower boiling point and a lower solubility of ammonia in it, which can reduce the time and temperature for removing ammonia, and the obtained catalyst also has a larger specific surface area and catalytic activity. The methanol, ethanol, ammonia and water that evaporate together during heating can also be reused, including reused after separation by distillation.

[0080] In Example 9, a small amount of carbon dioxide is introduced during the ammonia evaporation process to supplement carbonate ions, thereby stabilizing highly active intermediates such as zinc malachite, thereby improving various aspects of catalytic performance. However, the acidity brought by the supplementation of carbon dioxide will reduce the free ammonia content in the solution, resulting in a decrease in ammonia partial pressure and a longer time required for ammonia removal.

[0081] Comparing the embodiment with comparative example 1, it can be found that the performance of the catalyst prepared by the ammonia circulation method is relatively similar to that of the catalyst prepared by the coprecipitation method. After optimizing the preparation conditions, the performance of the catalyst prepared by the ammonia circulation method is better. However, comparative example 1 cannot realize the recycling of raw materials on the one hand, and on the other hand, it will produce nitrogen oxides and wastewater containing sodium nitrate. Moreover, if copper nitrate or zinc acetate is prepared using metallic copper or metallic zinc as a precursor, nitric acid or acetic acid is required for dissolution. When impurities such as silicon oxide, aluminum oxide, iron oxide, and calcium carbonate are present, the product in the preparation process will have more impurities, so the purity of the raw materials is required to be relatively high.

[0082] Comparing the embodiment with comparative example 2, it can be found that the product of comparative example 2 has significantly decreased performance in all aspects, which shows that whether it is zirconium oxide, aluminum oxide, magnesium oxide or other additives, they all have the effect of increasing the specific surface area of ​​the catalyst, while the copper-zinc catalyst without additives has a smaller specific surface area and poorer catalytic performance. Different additives can improve the performance of the catalyst in different aspects and have their own advantages.

[0083] Comparing Examples 1, 7 and 8, the addition of different additives to the three results in different catalyst performance results. Alumina, as a structural additive, can disperse copper and zinc; zirconium oxide can activate carbon dioxide, so the reaction conversion rate and methanol space-time yield are both high; and magnesium oxide has a strong alkalinity, which helps to improve methanol selectivity.

[0084] By comparing the example with comparative example 3, it can be found that the synergistic effect of copper and zinc is crucial to the catalytic performance. In the absence of zinc, the catalytic performance of the copper-based catalyst alone is poor, significantly lower than that of the copper-zinc-based catalyst.

[0085] The above is an exemplary description of the present invention. Obviously, the specific implementation of the present invention is not limited to the above-mentioned method. As long as various non-substantial improvements are made using the inventive concept and technical solution of the present invention, or the inventive concept and technical solution are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A method for preparing a copper-zinc-based catalyst synthesized by an ammonia circulation method, characterized in that: include: Dissolving a copper-containing solid, a zinc-containing solid and an ammonia-containing substance in a solvent, and obtaining a copper-ammonia-zinc-ammonia solution after filtering; adding an auxiliary agent to the copper ammonia-zinc ammonia solution; The copper ammonia-zinc ammonia solution is heated, and water vapor or carbon dioxide or a mixture of the two is introduced at the same time, and vacuum is drawn to maintain negative pressure, so that the ammonia is gasified and separated from the solution system, and precipitation is generated in the solution. The gasified ammonia obtained by vacuum drawing is condensed or washed with water to generate ammonia water and recycled; The precipitate is filtered out and the filter cake is washed with deionized water. The filter cake is dried, calcined and pressed into a shape to obtain a catalyst.

2. The method for preparing a copper-zinc based catalyst synthesized by an ammonia circulation method according to claim 1, characterized in that: The auxiliary agent includes any one of aluminum oxide, aluminum hydroxide, aluminum nitrate, zirconium oxide, zirconium hydroxide, zirconium nitrate, magnesium oxide, magnesium hydroxide, and magnesium nitrate, or a mixture of several of them.

3. The method for preparing a copper-zinc based catalyst synthesized by an ammonia circulation method according to claim 1, characterized in that: The solvent is any one of water, methanol and ethanol or a mixture of several of them.

4. The method for preparing a copper-zinc based catalyst synthesized by an ammonia circulation method according to claim 1, characterized in that: The ammonia-containing substance is any one of ammonia, ammonium carbonate, ammonium bicarbonate and urea or a mixture of several of them.

5. The method for preparing a copper-zinc based catalyst synthesized by an ammonia circulation method according to claim 1, characterized in that: The copper-containing solid is any one or a mixture of metallic copper, copper oxide, cuprous oxide, copper hydroxide, cuprous hydroxide, basic copper carbonate, copper nitrate and copper ore.

6. The method for preparing a copper-zinc based catalyst synthesized by an ammonia circulation method according to claim 1, characterized in that: The zinc-containing solid is any one of metallic zinc, zinc oxide, zinc hydroxide, zinc carbonate, basic zinc carbonate, zinc nitrate and zinc ore or a mixture of several thereof.

7. The method for preparing a copper-zinc based catalyst synthesized by an ammonia circulation method according to claim 1, characterized in that: The heating temperature of the copper ammonia-zinc ammonia solution is controlled between 45-90°C, and the vacuum degree is controlled between 0.01-0.1MPa during vacuuming.

8. The method for preparing a copper-zinc based catalyst synthesized by an ammonia circulation method according to claim 1, characterized in that: The drying temperature of the filter cake is 60-150°C, and the calcination temperature is 280-350°C.

Citation Information

Patent Citations

  • Method for preparing high-purity active copper oxide by secondary ammonia distillation method of alkaline etching solution

    CN111747440A

  • Preparation method and application of high-purity aurichalcite Cu2Zn3 (OH) 6 (CO3) 2

    CN116199250A

  • Copper-based catalyst as well as preparation method and application thereof

    CN118079932A

  • Preparation method of copper-based catalyst for synthesizing cyclohexanone through cyclohexanol dehydrogenation

    CN118416892A